Library Utilization and Services at Kota Kinabalu Indonesian School - Mohamed Rafi, Sharmili (Siber International Journal of Education Technology (SIJET), 2023)
This study aims to get an overview of services to library visitors at the Kota Kinabalu Indonesian School . This type of research is descriptive quantitative research. Data processing techniques use percentage formula statistical techniques. The research findings show that there is still a lack of collections of library materials because the existing collections are not sufficient to meet students' needs, catalogs and classifications have not gone well so that students have difficulty finding the books they want. Services and guidance to readers in the use of the library provided by librarians have been carried out however, at the stage of using the library as a learning resource in general students have used the library a lot on the students' own awareness.